Augmented reality (AR) marketing and consumer responses: A study of cue-utilization and habituation - Söderström, Charlotte; Mikalef, Patrick; Dypvik Landmark, Andreas; Gupta, Shivam (Journal of business research, 2024)
While Augmented reality (AR) enables consumers to experience a more vivid and entertaining shopping experience, there is limited empirical knowledge on how this technology influences behavioral consumer responses, particularly over time. This study builds on cue-utilization and habituation theories to understand if the proposed effects are subject to erosion over repeated use of AR applications. To evaluate the hypotheses, we conducted a study with users of an AR marketing app in the USA. Perceptions of usefulness are most important for first-time users when it comes to purchase intention. Contrarily, for habitual users’, enjoyment was found to be the most important factor. In addition, we find that vividness has a stronger effect on affective responses for first-time users compared to habitual users, and augmentation exerts a stronger effect for habitual users on their cognitive and affective responses.